Sustained Transmission of Neisseria gonorrhoeae Strains with High-Level Azithromycin Resistance (MIC ≥ 256 μg/mL) in Argentina, 2018 to 2022 - Ricardo Ariel Gianecini; Tomas Poklepovich; Daniel Golparian; Noelia Cuenca; Laura Scocozza; Silvina Bergese; Liliana Fernández Canigia; Viviana Vilches; María Julia Lazzarino Elgart; Magnus Unemo; Josefina Campos; Patricia Galarza (Microbiology Spectrum, 2023)
ABSTRACT Azithromycin combined with ceftriaxone is the recommended dual therapy for uncomplicated gonorrhea in many countries. Nevertheless, the increasing prevalence of azithromycin resistance compromises the effectiveness of this treatment strategy. From 2018 to 2022, we collected 13 gonococcal isolates with high-level azithromycin resistance (MIC ≥ 256 μg/mL) across Argentina. Whole-genome sequencing revealed that these isolates were mainly represented by the internationally spreading Neisseria gonorrhoeae multi-antigen sequence typing (NG-MAST) genogroup G12302, containing the 23S rRNA A2059G mutation (in all four alleles) together with mosaic mtrD and mtrR promoter 2 loci. This information is important to develop targeted public health policies to control the spread of azithromycin-resistant N. gonorrhoeae in Argentina and internationally. IMPORTANCE Azithromycin resistance in Neisseria gonorrhoeae has been increasing in numerous populations worldwide, which is of concern, as azithromycin is part of the recommended dual treatment in many countries. Here, we report 13 N. gonorrhoeae isolates with high-level azithromycin resistance (MIC ≥ 256 μg/mL). This study observed that high-level azithromycin-resistant gonococcal strains have shown sustained transmission in Argentina and are related to the successful international clone NG-MAST G12302. Genomic surveillance together with real-time tracing and data-sharing networks will be crucial in controlling the spread of azithromycin resistance in gonococcus.